2022
DOI: 10.1039/d1ra08908k
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide decorated with gold enables efficient biophotovolatic cells incorporating photosystem I

Abstract: This paper describes the use of reduced graphene oxide decorated with gold nanoparticles as an efficient electron transport layer for solid-state biophotovoltic cells containing photosystem I as the sole photo-active component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…[8][9][10] In biohybrid photovoltaics, photoactive biocomponents are connected to arti-cial electrode materials to generate that photocurrent. Successful setups have been achieved with PSI, 1,5,7,[11][12][13][14][15] PSII, 9,[16][17][18][19][20][21] and bacterial reaction centers. 4,8,[22][23][24][25] But likewise, thylakoid membranes [26][27][28] and even whole cells [29][30][31][32] have been deployed effectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] In biohybrid photovoltaics, photoactive biocomponents are connected to arti-cial electrode materials to generate that photocurrent. Successful setups have been achieved with PSI, 1,5,7,[11][12][13][14][15] PSII, 9,[16][17][18][19][20][21] and bacterial reaction centers. 4,8,[22][23][24][25] But likewise, thylakoid membranes [26][27][28] and even whole cells [29][30][31][32] have been deployed effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Many electrode materials and constructions have been applied as the synthetic part in contact with the biological entity. Metals, alloys, and metal oxides such as gold, 8,11,24,33,34 silver, 22 indium bismuth tin, 31 antimony tin oxide (ATO), 25,35 indium tin oxide (ITO), 14,21,28,[36][37][38] titanium dioxide, 16,20,39,40 zinc oxide, 8,29 and zirconium dioxide 39 as well as many carbon-based materials 1,11,21,41,42 have been utilized successfully. It is important to note that not only at 2D electrodes have been produced, 24,34,43 but also thicker architectures including multilayers, 13,14,24,33 hydrogels, 1,7,23 and 3D setups.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting holes in P 700 can also move to the adjacent electron‐donor materials. Due to the proper value of optical gap (calculated in the previous section) and the proper location of photosystem energy levels, well‐known electron transfer layers such as C60, [ 30 ] graphene oxide, [ 31 ] and PEDOT:PSS [ 32 ] can be used in biohybrid solar cells.…”
Section: Resultsmentioning
confidence: 99%
“…Natural light-harvesting complexes, such as the photosystem (PS), have drawn some attention in this direction because of their natural function in producing energy upon light excitation. Previous studies revealed the possibility of generating photocurrents using the PS protein and of utilizing the protein in photovoltaic devices , and solar cells. The use of the PS protein in such devices requires a deposition process of the PS, resulting in a monolayer or a multilayer film, and thus, it has to be formed on a surface, such as an electrode or gold nanoparticle . Furthermore, in most studies, the photocurrent generation was achieved in an electrochemical setup, i.e., in an aqueous solution, which can be a limiting factor.…”
Section: Introductionmentioning
confidence: 99%